2023
DOI: 10.1371/journal.pbio.3001959
|View full text |Cite
|
Sign up to set email alerts
|

LRRC15 mediates an accessory interaction with the SARS-CoV-2 spike protein

Abstract: The interactions between Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and human host factors enable the virus to propagate infections that lead to Coronavirus Disease 2019 (COVID-19). The spike protein is the largest structural component of the virus and mediates interactions essential for infection, including with the primary angiotensin-converting enzyme 2 (ACE2) receptor. We performed two independent cell-based systematic screens to determine whether there are additional proteins by which th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 95 publications
0
19
0
Order By: Relevance
“…LRRC15 expression was associated with inflamed conditions such as cancer, autoimmunity and inflammatory diseases [ 123 ]. Through a whole-genome CRISPR activation screening approach, LRRC15 was found to bind to SARS-CoV-2 spike [ 124 , 125 , 126 ]. This interaction was confirmed in vitro.…”
Section: Sars-cov-2 Alternative Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…LRRC15 expression was associated with inflamed conditions such as cancer, autoimmunity and inflammatory diseases [ 123 ]. Through a whole-genome CRISPR activation screening approach, LRRC15 was found to bind to SARS-CoV-2 spike [ 124 , 125 , 126 ]. This interaction was confirmed in vitro.…”
Section: Sars-cov-2 Alternative Receptorsmentioning
confidence: 99%
“…This interaction was confirmed in vitro. The interaction involved RBD domain [ 125 , 126 ]. Interestingly, LRRC15 did not facilitate entry of the virus but it was found to inhibit infection of permissive cells.…”
Section: Sars-cov-2 Alternative Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It is noteworthy to mention that the binding of SARS-CoV-2 differs from any other previously studied spikebinding viruses. 4 However, due to the similarity between SARS-CoV-1 and SARS CoV-2 sequences, Angiotensinconverting enzyme 2 (ACE2) has been identified as one of the primary S protein binding receptors, possessing higher affinity for the later, thereby considered a contributing factor for its increased pathogenicity. 3,5,6 The S1 subunit, among the two S protein subunits, has been studied in depth and shown to possess strong binding affinities toward various host cell receptors, when the S2 subunit enables the viral membrane to fuse into the host cell membrane, admitting the virus inside.…”
mentioning
confidence: 99%
“…11 Recent studies have advocated that the Leucine-rich repeat containing protein 15 (LRRC15) receptor, a member of the horseshoe shaped Leucine-rich repeats (LRR) family of receptors may also contribute greatly toward the SARS-CoV-2 infectivity by inducing spike binding. 4 Earlier this year, a study of public expression data sets by Shilts et al remarkably revealed the unique binding pattern of LRRC15 specific to only SARS-CoV-2 among all the coronaviruses; LRRC15 is also able to bind to SARS-CoV-1 spike upon deglycosylation, but with less accessibility than SARS-CoV-2. 4 LRRC15 shows significant binding affinity with the RBD of the S protein to facilitate viral entry within the host.…”
mentioning
confidence: 99%